Optimization of the tourist route by solving the problem of a salesman - Shynkarenko, Larysa; Shinkarenko, Vladimir; Nezdoyminov, Sergii; Galasyuk, Svetlana (My University, 2020)
The article is devoted to the problem of constructing the optimal transport route of a bus excursion tour of a tour operator according to the minimal length criterion. Transportation expenses are an important part of a bus tour cost, and their minimization is a required condition for route development and planning. To solve this problem, the authors used the tour route calculating method as a kind of transport task, namely the task of the salesman. To solve this problem, one of the varieties of the transport problem, namely the salesman traveling problem, is applied. The essence of the traveling salesman problem is to find the shortest route between cities, if the distances between them are known. The beginning of the route and its end coincide, that is, the route is cyclic. The most popular in Ukraine sightseeing tours of tour operators to the Transcarpathian region are taken for the optimization. A mathematical model of the traveling salesman problem is made to construct an optimal transport route. The solution was found using the Microsoft Excel’s Solver add-in application program package. To solve the problem by this method, it was reduced to a special form and additional variables were introduced. The analysis helped the tour operator to check the existing sightseeing bus routes by the minimal length criterion. The results allowed making assumptions about the need to change some popular routes of Ukrainian tour operators in order to reduce transport costs. The method of bus tours evaluation of tour operators according to the minimal length criterion allows to check the tourist transportation optimality while planning the route and developing their own tourist product. The introduction of modern digital technologies and software to optimize the territorial organization of tourist routes is proposed, which will help tour operators of Ukraine in the design of bus tourist trips to nature and recreational locations in tourist regions. The development of an optimal model for the transportation of tourists on the highways and the reduction of their costs for consumption of transport services will contribute to the development of tourist trips in Ukraine. The necessity of using methods of geolocation of tourist resources for the construction of routes for visiting natural and cultural-historical monuments and tourist centers has been determined. The application of the proposed method will allow tour operators to reduce transport costs and, as a consequence, the total cost of the tourist product.
Shinkarenko Vladimir Optimization of the tourist route by solving the problem of a salesman / Vladimir Shinkarenko, Sergii Nezdoyminov, Svetlana Galasyuk, Larysa Shynkarenko // Journal of Geology, Geography and Geoecology. - 2020. – Vol. 29, No 3. - P. 572-579. doi: 10.15421/112052
Keywords: tourist route; Transcarpathian region; tour operator; traveling salesman problem; optimization; solution search